BODY MASS INDEX IN ISCHEMIC HEART DISEASE AND SHORT-TERM OUTCOMES OF CORONARY BYPASS GRAFTING - A. N. Sumin; A. V. Bezdenezhnykh; S. V. Ivanov; O. L. Barbarash (Российский кардиологический журнал, 2015)
Aim. To study relation of body mass index and short term results of coronary bypass grafting (CBG).Material and methods. 1490 CBG patients, were selected to groups according to body mass index (BMI): normal body mass (BMI 18,5-24,9 kg/m2, n=351), overweight (BMI 25-29,9 kg/m2, n=658), first grade obesity (BMI 30-34,9 kg/m2, n=409), second grade obesity (BMI 35-39,9 kg/m2, n=72). The groups were equal by clinical data and anamnesis, laboratory and instrumental data. also we evaluated the prevalence of post operation complications and perioperational mortality. The relation of possible factors with the chance of complications to be found assessed via logistic regression model.Results. The groups were comparable in age, prevalence and anamnesis of vascular catastrophes, severity of CHD and CHF. Part of men decreased with the increase of BMI (p<0,001). Diabetes of 2nd type and AH were more prevalent among patients with higher BMI (in all cases p<0,001). With BMI increase there was significant increase of triglycerides level and HDL cholesterol decrease (p<0,001 and p=0,004, resp.). Glomerular filtration rate, by MDRD, was lower in obesity groups. On-pump operation was done in 1287 (86,4%) cases. More often in groups with higher BMI the radiofrequency ablation was performed (p=0,006), and in these groups also the post operation period complicated with atrial fibrillation (p=0,001). In monofactorial logistic regression analysis the chance of complications increased with the decrease of GFR (p=0,021), age increase (p<0,001), in on-pump operation (p=0,004) and its duration (p<0,001). Age and duration of on-pump also were significant in multifactorial analysis (p<0,001 and p=0,015, resp.). Chance of fatal outcome increased with the duration of on-pump (p<0,001) and decrease of LVEF (p=0,001). These factors also showed significant contribution on the chance of fatal outcome, and in multifactor analysis — the duration.Conclusion. Increase of BMI is associated with the prevalence of arterial hypertension and diabetes mellitus, triglycerides increase, enlargement of the left atrium, HDL decrease and GFR. Among patients with obesity there was only increase of atrial fibrillation prevalence growth during post-operational period.